ASME 2008 International Manufacturing Science and Engineering Conference, Volume 2 2008
DOI: 10.1115/msec_icmp2008-72193
|View full text |Cite
|
Sign up to set email alerts
|

Material Characterization of Uncoated Boron Steel for Automotive Body Structure Applications

Abstract: Use of Advanced High Strength Steels in automotive applications is increasing. One of these materials is boron steel, which is commercially available in coated and uncoated sheets. Automotive manufacturers are using boron steel in body structure applications to produce light weight parts and to address safety requirements. Boron steel is available in a non heat-treated condition (also referred to as “green state”) which typically has a yield strength around 350 MPa. The yield strength for a fully temperature h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was suggested that the higher boron content steel resulted in a larger weld because it exhibited a higher contact resistance during resistance seam welding. A new generation of borontreated automotive steels are currently of interest because they can be hot stamped and subsequently quenched to produce a martensitic structure with high strength, typically in the range of 900 to 1200 MPa [17]. Studies on the effect of boron content on the weldability of high-strength steels indicate that increasing boron concentration above 100 ppm in the weld metal results in cracking [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the higher boron content steel resulted in a larger weld because it exhibited a higher contact resistance during resistance seam welding. A new generation of borontreated automotive steels are currently of interest because they can be hot stamped and subsequently quenched to produce a martensitic structure with high strength, typically in the range of 900 to 1200 MPa [17]. Studies on the effect of boron content on the weldability of high-strength steels indicate that increasing boron concentration above 100 ppm in the weld metal results in cracking [18].…”
Section: Introductionmentioning
confidence: 99%